2012
DOI: 10.1055/s-0032-1306425
|View full text |Cite
|
Sign up to set email alerts
|

Hypercoagulation and Thrombophilia in Nonalcoholic Fatty Liver Disease: Mechanisms, Human Evidence, Therapeutic Implications, and Preventive Implications

Abstract: Nonalcoholic fatty liver disease (NAFLD) is a spectrum of disorders with a high prevalence in the industrialized world. Despite the high prevalence, the etiology and fundamental pathophysiology for the disease process is poorly understood. There is now a growing fund of knowledge suggesting that the ongoing inflammatory state associated with NAFLD leads to a low-level activation of the coagulation system. Although the data supporting this activation of the coagulation system are significant, the link with end-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 110 publications
(127 reference statements)
2
38
0
4
Order By: Relevance
“…A diagnosis of fatty liver or cryptogenic liver disease was associated with the highest OR of PVT (1.5), and lends support to the suggested association of fatty liver and obesity with increased thrombotic risk. [17][18][19] These same risk factors were also associated with presence of PVT at listing, lending further credibility to their association with risk for PVT. Ascites was also associated with risk of "new" PVT, which concurs with the association of increased risk of PVT with lower portal flow in the setting of more severe portal hypertension.…”
Section: Discussionmentioning
confidence: 62%
“…A diagnosis of fatty liver or cryptogenic liver disease was associated with the highest OR of PVT (1.5), and lends support to the suggested association of fatty liver and obesity with increased thrombotic risk. [17][18][19] These same risk factors were also associated with presence of PVT at listing, lending further credibility to their association with risk for PVT. Ascites was also associated with risk of "new" PVT, which concurs with the association of increased risk of PVT with lower portal flow in the setting of more severe portal hypertension.…”
Section: Discussionmentioning
confidence: 62%
“…Interestingly, liver cirrhosis is associated not only with a bleeding tendency but also with a hypercoagulation status due to the decreased synthesis of anticoagulant factors or impaired degradation of prothrombotic factors 20. We are not aware of any specific data showing that liver cirrhosis independently contributes to a higher risk of ischemic stroke in AF, but as our population profile shows, such patients are at high risk given the associated comorbidities and high CHA 2 DS 2 VASc scores.…”
Section: Discussionmentioning
confidence: 79%
“…In patients with chronic liver disease, the common background for both complications seems to be shared specifically in non-alcoholic fatty liver disease (NAFLD) as studies have shown this group of patients to be at risk for both complications [40,41]. However, cardiovascular diseases are the leading cause of macrovascular-related morbidity and mortality in NAFLD [42].…”
Section: Arterial Thrombosismentioning
confidence: 99%